Reflections on Spanish scholarly journals - Giménez-Toledo, Elea (Anuario ThinkEPI, 2013)
The current ease of online publishing has led to an excess of e-journals, all struggling to attract manuscripts and to survive, and most often without success. This fragile situation for journals means that when one of them does climb up in the quality rankings it is likely to be absorbed by a large foreign publisher. The article reflects on the academic world's dependence on international commercial databases, and questions the Spanish government's expenditure on subscriptions to them. Finally, a recent campaign conducted against Elsevier is described.
Keywords: Academic journals; Scholarly journals; Elsevier; Spain; Publishers; Publishing market; Situation analysis.